Pengembangan Sistem Penjualanan LampOrder Berbasis Web Menggunakan Metode System Development Life Cycle (SDLC) - Hidayanto, Pradana Wahyu; Voutama, Apriade (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
The rapid development of technology in the business world increases the efficiency and effectiveness of stores. In this article, to help the LampOrder website to store its data, the database uses MySQL as a storage medium. In addition, it can reduce errors and data loss when processing sales data. The website can also be a promotional medium to promote the latest quality products to improve the sales graph on the LampOrder website. When designing a web-based system infrastructure, design modeling is required, namely the Unified Modeling Language (UML). UML is modeled to support the system design process to reduce errors when creating a website. UML applications describe the structure of the actors involved, the activities of individual actors, the processes and mechanisms of the ordering system. The use of UML modeling simplifies the design by supporting the coding process in a website-based lamp ordering system. With this program, it can facilitate buying and selling transactions for both sellers and customers.